Halal restaurant finder / Khairol Azahar Ramli - Ramli, Khairol Azahar (2014)
Nowadays, the number of restaurants in urban area is increasing drastically. This is because of the increasing numbers of the tourist to that particular area. Apart of providing different kind of services and cuisines, they are also located in different area. These conditions lead to major problem which is difficulty to find Halal restaurants among the Muslim tourist. A mobile application with Android platform was develop to help tourists in searching for Halal restaurant. Ipoh, Perak is selected as this project's case study. The application provides the information of Halal restaurants in Ipoh, Perak and also the shortest path to go to the restaurants using Google Maps and GPS. A Dijkstra algorithm technique is chosen in order to implement the shortest path to the venue chosen. By using this application, tourists can get information about Halal restaurants in Ipoh. Besides that, they can find the fastest route to the chosen restaurant by using the shortest path provided in the application. For this application, a survey has been conducted before and after the development of this application. The outcomes of the survey, most of the respondents are interested in Halal restaurant application and they are very satisfied with the function and interface design of Halal Restaurant Finder application. In future, this application needs to widen up the area (not only in Ipoh, Perak) and also improves the application features and the interface design.